Reproductive Healthcare Services and the U.S. Supreme Court: beyond Roe v. Wade and 'Abortion Clinics' - Vergara, Karla (Revista de Investigações Constitucionais, 2017)
At a time when the United States is sharply divided on women's reproductive rights, the focus has shifted from legality to that of access to reproductive healthcare services. This debate is too often defined by the pro-choice/anti-choice binary. This binary overlooks women who seek reproductive healthcare services for reasons other than abortion (such as pap smears, gynecological check-ups, birth control, STD testing, breast cancer preventive screenings, etc.). Self-proclaimed sidewalk counselors approach these women to convince them that there are alternatives to abortion. While some women may welcome a sidewalk counselor's approach, the women who choose to ignore them more often than not risk being scolded, yelled at, harassed, and humiliated publicly. These interactions leave many of these women shaken, nervous, and deterred from seeking necessary reproductive healthcare services. Many states have enacted buffer zone legislation to protect women trying to access reproductive healthcare clinics, but an overwhelming amount of these laws have been struck down on a First Amendment basis. The Supreme Court has decided these cases without defining who qualifies as a sidewalk counselor and who is properly deemed a more threatening protester against whom a legal action may be brought. This has caused great uncertainty in the law. This paper argues that sidewalk counselors and activists’ protesting against abortion outside of these clinics is futile. Reproductive healthcare clinics offer a wide range of services—not just abortions. Therefore, it is impossible for anti-abortion activists to ascertain who is seeking an abortion and who is not without intruding into women’s personal reproductive choices and medical needs. Buffer zones around reproductive healthcare facilities help protect women’s privacy and their right to access so they may obtain the reproductive healthcare they are entitled to receive.